Lipid intermediates in protein glycosylation - Parodi, Armando José A. (1976)
The oligosaccharide moieties of animal glycoproteins that involve linkage between carbohydrate and asparagine are built up on dolichol pyrophosphate before incorporation into the protein. The use of dolichol pyrophosphate in place of the commoner nucleoside diphosphate as the sugar carrier may be because the former is more compatible with the hydrophobic environment of the membrane where the glycoprotein synthesis occurs.